The Determinants of Startup Risk in Indonesia: A Bibliometrical Analysis - Zulfikar , Ian; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research presents a bibliometric analysis of startup risk in Indonesia based on scientific publications from 2015 to 2023. Data was obtained from Google Scholar with the keyword "Startup Risk in Indonesia" in English or Indonesian language publications. Analysis using the VOSviewer tool involves keyword, co-word and citation frequency analysis techniques to identify trends in startup risks. The research results include 95 scientific articles that highlight the risks of startups in Indonesia. Citation analysis shows the high influence of these articles with a total of 95 citations in 100 selected journals. The article with the highest citations is "The role of fintech in increasing financial inclusion for MSMEs in Indonesia (sharia financial approach)" (2018) with 348 citations. Visualization using VOSviewer produces a network map with six clusters, highlighting research focuses such as the development of startups, SMEs and industry. Keyword overlay analysis shows a change in trends from sectors and SMEs in 2018 to a focus on startup keywords in 2022. The density visualization highlights themes that require more exploration, including "startup companies," "startups in Indonesia," and " fintech." These results provide in-depth insight into the trends and focus of startup risk research in Indonesia, providing an important contribution in the growth and development of startups as well as academic literature related to startup risks in this country